PERAN GURU DALAM MENUMBUHKAN ETIKA DAN MORAL SISWA SDN 006 MUKTI JAYA ROKAN HILIR - Evi Setiyawati; Siti Quratul Ain (STKIP Subang, 2025)
This study aims to describe the role of teachers in fostering students’ ethics and morals at SDN 006 Mukti Jaya, Rokan Hilir. The research is grounded in the growing decline in students’ ethical and moral behavior, reflected in impolite attitudes, low discipline, the use of inappropriate language, and a lack of respect toward teachers and peers. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The research subjects consist of six teachers and six students who serve as key informants. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that teachers play a crucial role in developing students’ ethics and morals through five major roles: as educators and instructors, mediators and facilitators, role models, motivators, and as guides and evaluators. Teachers instill ethical values through exemplary behavior, positive habituation, motivation, and the creation of a supportive learning environment. Furthermore, teachers address moral violations through personal guidance, counseling, and explanations regarding responsibility and respectful behavior. However, the study also identifies several inhibiting factors, including exposure to social media, peer influence, and inadequate parental support. This study concludes that teachers hold a significant role in shaping students’ character, yet stronger collaboration between schools, families, and the community is needed to ensure optimal ethical and moral development.